2021
DOI: 10.3389/fpls.2021.659645
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Transcriptomic Profiling of Tetrastigma hemsleyanum Fully Developed Tuberous Roots Enriches Candidate Genes in Essential Metabolic Pathways and Phytohormone Signaling

Abstract: Tetrastigma hemsleyanum Diels et Gilg (Sanyeqing, SYQ) is a perennial climbing liana and an endemic plant to southern China. Its tuberous roots (TRs) are used in traditional Chinese medicine for treating some diseases such as high fever, pneumonia, asthma, hepatitis, and cancers. However, the mechanisms underlying the development of TR and the content of flavonoids and phenylpropanoids (FPs) are not well-understood. In this study, we performed a transcriptomic analysis of 12 fully developed TR (FD-TR) samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…The total phenol content was determined by the Folin‐Ciocalteu method by microplate reader (Spectramax 190, USA) [31] . The total flavonoid content was determined by the aluminum nitrate colorimetric method [32] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total phenol content was determined by the Folin‐Ciocalteu method by microplate reader (Spectramax 190, USA) [31] . The total flavonoid content was determined by the aluminum nitrate colorimetric method [32] …”
Section: Methodsmentioning
confidence: 99%
“…[31] The total flavonoid content was determined by the aluminum nitrate colorimetric method. [32] Total Polysaccharide Content Assay…”
Section: Total Phenolic and Total Flavonoid Content Assaymentioning
confidence: 99%
“…The total phenolic content was expressed as milligram of gallic acid equivalent per gram of herbal mixture. The determination of total flavonoids was performed by NaNO 2 -Al(NO 3 ) 3 -NaOH colorimetric method with rutin as a standard for estimating the content of total flavonoids ( 31 ). After determination, the concentration of total polysaccharide, total saponins, total polyphenols and total flavonoids in the herbal mixture were 70.5, and 24.8, 13.0, and 26.2 mg/g, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Artemisinin biosynthetic pathway was also activated by chilling stress in Artemisia annua (Vashisth et al, 2018). Interestingly, the flavonoids and saponins content were more accumulated in the root of Tetrastigma hemsleyanum (Xiang et al, 2021) and Panax notoginseng (Xia et al, 2017), respectively, when the transformation occurred from Summer to Autumn. While Carpenter et al (2014) not only demonstrated the reddening of L. japonica leaves, but also revealed the relationship between the photoprotective function of anthocyanin and leaves reddening.…”
Section: Introductionmentioning
confidence: 99%